SETTLE DOWN: Preliminary investigations and development of an online toolkit to support student self-regulation in higher education - Keane, Carol A.; Miller, Leonie M.; Eady, Michelle J.; Green, Corinne A. (Frontiers in Education, 2022)
The impact of stressors on student well-being and academic performance is widely documented within the Higher Education sector, with student drop-out rates linked to poor well-being. Identified connections between attrition rates and levels of support offered to students has led to concerted efforts to better support student well-being – particularly for those in the first year of study. The COVID-19 pandemic and the rapid and abrupt shift toward online learning has complicated how students manage stress by reducing students’ access to the very resources that might otherwise buffer them (e.g. social connection) exposing them to risk factors (e.g. isolation and greater uncertainty). Accordingly, empowering students to better self-regulate during stressful times is, more than ever, essential to supporting the transition to the adult learning environment. The development of students’ self-awareness and self-knowledge of the influences of being stressed on their engagement in study is an important adjunct to self-regulated learning. This nexus between psychology and education is a point for an interventive program that meets a gap in current support efforts, and that recognises the need for such endeavours that situate within the digital landscape of Higher Education. In this paper we describe the groundwork of a single cohort case study that outlines a novel approach to student well-being. We discuss the design and development process of the SETTLE DOWN program; an evidence-based and clinically informed series of self-regulation workshops for undergraduate students, which aimed to foster student self-awareness about personal stress responses, facilitate a guided self-discovery of self-regulation techniques, and embed self-knowledge through reflection and practice. Preliminary pilot data is presented with respect to the intended purpose of assessing the suitability of the program material to achieve desired outcomes. The translation of these workshops into an online format to maximise accessibility for students and teachers is extrapolated in discussion of future-directions and next steps for the SETTLE DOWN program. The case study offers an example of the development of an evidence-based approach to ultimately support students with online availability of the necessary knowledge and skills to foster self-awareness and self-knowledge in the context of engaging in study under stress.